2013
DOI: 10.7812/tpp/12-130
|View full text |Cite
|
Sign up to set email alerts
|

Elimination of Admission Hypothermia in Preterm Very Low-Birth-Weight Infants by Standardization of Delivery Room Management

Abstract: We reduced hypothermia in very low-birth-weight infants using a standardized protocol, multidisciplinary team approach, and continuous feedback. Sustaining improvement is a challenge that requires real-time progress evaluation of outcomes and ongoing staff education.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
66
2
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(75 citation statements)
references
References 5 publications
1
66
2
6
Order By: Relevance
“…42,43,48,66 One small randomized clinical trial 78 (very-low-quality evidence, downgraded for indirectness and serious imprecision) showed a reduction in adverse events, including death, intracranial hemorrhage, necrotizing enterocolitis, and oxygen dependence with improved temperature management, but 3 randomized controlled trials [79][80][81] (low-quality evidence, downgraded for indirectness and imprecision) did not show any significant improvement in mortality with significantly improved temperature control. Four observational studies 60,61,63,82 (very-low-quality evidence, downgraded for indirectness and imprecision) did not find any improvement in mortality with improved admission temperatures, but they were not sufficiently powered for this outcome.…”
Section: Consensus On Sciencementioning
confidence: 99%
“…42,43,48,66 One small randomized clinical trial 78 (very-low-quality evidence, downgraded for indirectness and serious imprecision) showed a reduction in adverse events, including death, intracranial hemorrhage, necrotizing enterocolitis, and oxygen dependence with improved temperature management, but 3 randomized controlled trials [79][80][81] (low-quality evidence, downgraded for indirectness and imprecision) did not show any significant improvement in mortality with significantly improved temperature control. Four observational studies 60,61,63,82 (very-low-quality evidence, downgraded for indirectness and imprecision) did not find any improvement in mortality with improved admission temperatures, but they were not sufficiently powered for this outcome.…”
Section: Consensus On Sciencementioning
confidence: 99%
“…If effort is made to adjust the delivery room ambient air temperature prior to each delivery, along with implementing other thermal stability interventions, it is possible to completely eliminate the incidence of hypothermia as one group did in a quality improvement project over several years. 20 …”
Section: Delivery Room Temperaturementioning
confidence: 99%
“…Recently, a few quality improvement projects have been published where clinicians have attempted to bundle thermal interventions and evaluate body temperature in premature infants after birth. Manani et al report that they eliminated hypothermia in a cohort of 20 Targeting an admission temperature between 36°C and 37°C, the clinicians investigated the source of their thermal stability problems through root cause analysis, then implemented thermal guidelines incorporating use of a prewarmed resuscitation bed, polyethylene occlusive wrap, chemically activated warming mattress, warming lights during initial admission, newborn hat, and warmed blankets. They also aimed to increase delivery room temperature $25°C.…”
Section: Combining Interventionsmentioning
confidence: 99%
“…A report that used a standardized multidisciplinary approach in which a chemically activated heated mattress is combined with other techniques, such as polyethylene wraps, servocontrolled radiant warmer, warming light, newborn hats, and a well-trained dedicated team to monitor the axillary temperature every 5 minutes achieved success in preventing hypothermia in very low-birth-weight babies whose weight is below 1500 gm [31]. Hyperthermia was reported as an adverse effect in this protocol, and it was addressed by decreasing the temperature of beds during resuscitation from 37.5°C to 37°C and removing the polyethylene wrap after the admission temperature amounted to 36.5°C.…”
Section: Polyethylene Occlusive Wrapmentioning
confidence: 99%
“…Four randomized controlled trials concluded that hyperthermia isn't associated with plastic covering, while other studies that investigated the effect of plastic wrap among other procedures as a thermoregulatory bundle in Heated mattress: Conductive thermal mattress (CTM) has been found to be as efficacious as radiant warmer and other modes of warming that are often used as standards of thermal care. This was reported with regard to its short term use [30], however further trials are required to assess the long-term effects.A report that used a standardized multidisciplinary approach in which a chemically activated heated mattress is combined with other techniques, such as polyethylene wraps, servocontrolled radiant warmer, warming light, newborn hats, and a well-trained dedicated team to monitor the axillary temperature every 5 minutes achieved success in preventing hypothermia in very low-birth-weight babies whose weight is below 1500 gm [31]. Hyperthermia was reported as an adverse effect in this protocol, and it was addressed by decreasing the temperature of beds during resuscitation from 37.5°C to 37°C and removing the polyethylene wrap after the admission temperature amounted to 36.5°C.…”
mentioning
confidence: 99%